Kebermaknaan Hidup dan Mindfulness: Kunci Flourishing pada Wanita Karir? - Dewi, Nurfitriana Puspa; Salim, Agus; Warastri, Annisa (VISA: Journal of Vision and Ideas, 2024)
This study investigates the relationship between meaning in life and mindfulness with flourishing among career women. The sample consisted of 282 career women selected through purposive sampling. The research utilized scales measuring life meaning, mindfulness, and flourishing. Data analysis was performed using SPSS version 21. The findings revealed a significant positive correlation between life meaning and mindfulness with flourishing, with a significance level of 0.000. These results suggest that both life meaning and mindfulness are crucial in promoting the psychological well-being of career women. The study offers valuable insights into the factors contributing to flourishing in this population and may serve as a foundation for interventions aimed at enhancing their well-being.